Exploring the Values of Serat Wedharaga as an Acceleration of Empathy Strengthening in Guidance and Counseling - Indreswari, Henny; Bariyyah, Khairul; Probowati, Devy; Ilmi, Achmad Miftachul; Muyassirotul ‘Aliyah, Shabrina; Lisnanti, Anisa Ultari (Universitas Negeri Padang, 2023)
The lack of empathy shown by counselors towards their clients is a significant concern, as it can create discomfort and make clients reluctant to talk. To enhance empathy skills, it is essential to consider cultural aspects, one of which is drawing inspiration from the virtues contained in Serat Wedharaga to enrich the empathy abilities of prospective counselors. This study used a qualitative approach with a hermeneutic design, including data collection, analysis, and interpretation steps. The findings from the analysis of Serat Wedharaga have the potential to significantly contribute to improving counselor empathy. The study identified values such as humility, honesty, a learning spirit, responsibility, polite language, and perseverance. The main aspects of empathy, including social interaction, cognitive behavior, and emotional identification, were integrable with these values. For example, the values of humility and honesty in Serat Wedharaga support good communication skills in terms of social interaction. Similarly, the text’s spirit of learning and responsibility supports the understanding and imagination of others' views and perspectives in cognitive behavior. Additionally, the values of polite language and perseverance in Serat Wedharaga support the ability to feel and understand others' emotions in terms of emotional identification. These findings provide an essential basis for developing aspects of empathy that can be integrated with the concept of empathy, which can later be applied to enrich the guidance and counseling curriculum, including adding an empathy development course for prospective counselors.